Method of estimating sea‐surface paleotemperatures through biotic proxies: A case study in Upper Paleozoic paleoclimatic, paleogeographic and paleotectonic reconstructions of Siberia - Vladimir I. Davydov; Eugeny V. Karasev; Elizaveta V. Popova; Vladislav I. Poletaev (Ecology and Evolution)
Abstract This study introduces a novel approach for quantitatively assessing sea‐surface paleotemperatures examined in the Upper Paleozoic of Siberia, utilizing the obtained in the region data as a case study of the use of this method. The method relies on evaluating the taxonomic composition and ecological proxies of biota. It utilizes a comprehensive dataset encompassing the geographic distribution and ecology of various biotic groups in Siberia and adjacent regions, leveraging the newly developed by the authors large PaleoSib database and partially the Paleobiology Database (paleobiology.org) The taxonomy has been used according to the database of Global Biodiversity Information Facility (gbif.org). Fossils collected from individual locations often exhibit a wide spectrum of paleotemperatures. To address this variability, we developed an algorithm for calculating average biotic paleotemperatures in each locality/time slice. Our computations of the available data have unveiled a coherent pattern of paleoclimate dynamics, particularly Sea Surface Temperature, across Siberian basins and surrounding areas during the Late Paleozoic era. These findings significantly contribute to a refined comprehension of paleoclimate and paleotectonic dynamics in the region during that specific time. To enhance paleotemperature analyses, we have integrated lithological indices with biotic ones, fortifying the overall methodology and furnishing a more robust framework for interpreting paleoclimate data. The method could be a helpful tool in regional and interregional studies, regardless of the utilized rock's age and fossil groups.